EVALUATION OF THE RESULTS OF PARATHYROIDECTOMY IN CHILDREN WITH PRIMARY HYPERPARATHYROIDISM IN THE LONG TERM AFTER SURGERY - Nazira Rikhsieva (International Scientific and Current Research Conferences, 2021)
Primary hyperparathyroidism (PHPT) is a chronic endocrine disease characterized by excessive secretion of parathyroid hormone (PTH). Excessive secretion of PTH can be caused by adenoma, hyperplasia, or carcinoma of the parathyroid glands (PTG). The prevalence of PHPT increases with age, but the disease can affect people of all ages, including children. According to medical statistics, in families where there are patients with hyperparathyroidism, in 30% of cases, the disease manifests itself in children. It is generally accepted that surgery is the treatment of choice for the treatment of PНPT, which allows recovery in 92% of cases. Despite the undoubted successes of domestic and foreign scientists in the surgery of РНPT, associated with the study of the pathogenesis of this disease, the use of modern diagnostic methods and the improvement of surgical techniques, the results of surgical treatment are often unsatisfactory. In particular, in operated children there is no reliable information about the condition of patients in the long term after the intervention, the criteria for the effectiveness of surgical treatment of PGPT are still not clearly defined, as well as the relapse of primary hyperparathyroidism are quite formidable and can cause suffering to the child.